Comparison of levobupivacaine vs bupivacaine in thoracic spinal anaesthesia for laparoscopic cholecystectomies - Kour, Loveleen; Katoch, Madan Lal (International Journal of Research in Medical Sciences, 2019)
Background: Levobupivacaine is the pure S enantiomer of racemic bupivacaine. It is a long acting variant that is less toxic to the heart and central nervous system. It has gained relevance and popularity in the modern anaesthetic practice. Thoracic spinal anaesthesia has been shown to an effective and safe anaesthetic approach for a varied spectrum of surgeries including laparoscopic cholecystectomies. Incorporation of epidural catheter adds flexibility and the provision of postoperative analgesia. To adopt thoracic combined spinal epidural anaesthesia for laparoscopic cholecystectomies was chosen in the study. This study aimed at comparing the efficacy of levobupivacaine and bupivacaine in thoracic combined spinal epidural anaesthesia for laparoscopic cholecystectomies. Methods: Total 60 ASA 1 and 2 patients scheduled for laparoscopic cholecystectomies were chosen for the purpose of this study extending from January 2019 to May 2019. They were randomly divided into two groups - group L and group B. Both the groups received thoracic combined spinal anaesthesia using 2ml of 0.5% isobaric levobupivacaine and 25 µg (0.5ml) fentanyl in group L and 2ml of 0.5% isobaric bupivacaine and 25 µg (0.5ml) fentanyl in group B. The duration of sensory and motor block, peak block height, maximum motor block achieved, haemodynamic variables and any postoperative neurological complications were evaluated. Results: Both the groups showed similar onset of sensory and motor block. The duration of motor block was similar in both the drug groups; however, levobupivacaine showed a significantly loner duration of sensory block. There were no significant haemodynamic differences between the two groups and no postoperative neurological complications were seen in any patient. Conclusions: Levobupivacaine was found to be slightly better than bupivacaine in thoracic combined spinal epidural anaesthesia.